In vitro bioequivalence profile of Penicillin V tablets marketed in Kisangani, Democratic Republic of the Congo: Assay and dissolution kinetics of generic 250 mg and originator 600 mg - Rachel Ndezu Angirio; Jérémie MBINZE KINDENGE; Marguerite BORIVE AMANI; Francine UWIZEYIMANA; Jocelyn MANKULU KAKUMBA; Elodie NSASI BAKIANTIMA; Justin KADIMA NTOKAMUNDA; Roland MARINI DJANG'EING'A (Orapuh, Inc., 2024)
Introduction Phenoxymethylpenicillin is commonly presented in various generic forms and rarely as proprietary brands. Given the prevalence of counterfeit products and the increased use of generic drugs in sub-Saharan Africa, ensuring drug quality is critical to meet legal requirements for bioequivalence and interchangeable dispensation. Purpose The purpose of this in vitro study was to meticulously compare the bioequivalence of 250 mg generic Penicillin V tablets with an originator brand marketed in Kisangani, focusing on physicochemical properties and dissolution kinetics based on European Medicines Agency (EMA) standards and USP Pharmacopoeia (USP 43-NF 38, 2013) guidelines. Methods Identification and assay were performed using a UV-visible spectrophotometer, and dissolution kinetics were conducted at pH levels of 1.2, 4.5, and 6.8 with appropriate dissolution equipment. The fit factor method was applied to compare dissolution profiles across these pH levels. Results The findings are significant, revealing that while the generic tablets weighed half as much (340 mg) as the originator tablets (770 mg), both showed acceptable mass uniformity and contained approximately 250 mg of active ingredient. Dissolution profiles were comparable, with difference factors (f1) < 15 and similarity factors (f2) > 50. In acidic media (pH 1.2 and 4.5), full release occurred in under 15 minutes, while in basic intestinal-type medium (pH 6.8), an 80% release rate was observed. Conclusion These results support the interchangeability of the generic and originator Penicillin V products, while potential in vivo variations cannot be ruled out.